Peran Kualitas Produk, Host Live, dan Brand Awareness terhadap Penjualan Miso Butik melalui Live Shopee - Shinta Wahyuningrum; Satria Veriansyah Wiguna (GEMILANG: Jurnal Manajemen dan Akuntansi, 2026)
This research aims to analyze the role of product quality, live hosts, and brand awareness in influencing the sales performance of Miso Butik through Shopee Live. The increasing trend of online shopping has encouraged businesses to utilize live streaming as a more interactive marketing strategy. This research employs a descriptive qualitative approach with in-depth interviews focusing on Miso Butik’s Shopee Live activities. The findings indicate that product quality plays an essential role in building consumer trust and driving purchase decisions, while live hosts contribute to enhancing interaction and strengthening the emotional connection between the brand and customers. Furthermore, brand awareness formed through live streaming activities positively impacts customer loyalty. Overall, these three aspects are interrelated and have a significant influence on Miso Butik’s sales performance. The results of this study are expected to serve as a reference for online fashion businesses in optimizing their digital marketing strategies through Shopee Live.